THE ROLE AND SIGNIFICANCE OF HANDICRAFTS AND MUSEUM-WORKSHOPS IN THE DEVELOPMENT OF DOMESTIC AND INTERNATIONAL TOURISM (Modern American Journal of Social Sciences and Humanities, 2025)
This article examines the role of tourism in the socio-economic life of the country and the importance of handicrafts in the development of this sector, with particular attention to the Rishtan school of ceramics and the museum-workshops of the Fergana Valley. Furthermore, the paper discusses the opportunities provided by the state for the development of handicrafts and tourism, as well as the contributions of master potters who play an active role in advancing the sector.